The Limits of Institutional Reform in Development: Changing Rules for Realistic Solutions - Andrews, Matt (Cambridge University Press, 2013)
Institutional reforms are common across the globe. Think of efforts to build new governments in Afghanistan and Iraq; or decades worth of in terventions intended to improve fiscal management, reduce corruption o r introduce efficient public sector service delivery in African countr ies.These reforms often have limited results, however. They lead to ne w laws that are not properly implemented, and new organizations that h ave poor capacities and fail to function as needed. In this book, Matt Andrews explains why reform results are frequently limited and sugges ts ways to overcome these limits. In the first half of the book, Andre ws argues that reforms fail to make governments better when they are i ntroduced as signals to gain short-term support–from donors and others . Reforms as signals introduce unrealistic best practices that do not fit developing country contexts and are not considered relevant by imp lementing agents. The result is a set of new forms that do not functio n properly. Andrews uses examples to prove this point, ranging from ef forts to introduce fiscal rules in Argentina to reforms aimed at inter national accounting standard adoption in many African countries, and a nti corruption interventions in Malawi and Uganda. In the second half of the book, Andrews notes that there are instances where reforms are not being introduced as signals, and are having more of an impact on g overnment effectiveness. Examples include local government reforms in Rwanda, anti corruption initiatives in Indonesia, and a variety of ini tiatives ranging from results based management to civil service modern ization and internal control regime adoption in governments like Kenya , Kosovo and Afghanistan. Andrews uses these examples to discuss ways in which reforms can actually provide realistic solutions to governanc e challenges in developing countries. Lessons from these experiences s uggest that reform limits can be overcome by focusing interventions on problem solving, and promoting incremental and localized processes to find solutions, involving multiple agents who can authorize and imple ment reforms.